PERI-OPERATIVE MANAGEMENT OF ADULT TETRALOGY OF FALLOT - Naqvi, Shahab; Siddiqi, Rashad (Pakistan Armed Forces Medical Journal, 2006)
A 31-years old married soldier, weighing 57 Kg, was referred with a history of shortness of breath associated with chest pain since childhood that had increased over the last 3 years. He experienced dyspnea on mild to moderate exertion (NYHA - III). He was on oral propanolol 10mg thrice daily. On pre-operative investigations, his haemoglobin was 20.2 Gm/dL with 0.56 haematocrit. Echocardiography showed a patent foramen ovale, big ventricular septal defect, a 50% aortic over-ride with a right ventricular outflow tract obstruction and a pressure gradient of 80mmHg. Pre-operative chest radiograph revealed a hypertrophied right ventricle with oligaemic lungs.Oral premedication with benzodiazepine on the night before surgery and narcotic-based intra-muscular premedication was given before surgery. On arrival in the operation theatre, he had a regular pulse rate of 105 per minute, blood pressure 145/100mmHg and arterial oxygen saturation of 91-92% on air. Anesthetic management included ketamine-based induction technique with endotracheal intubation and positive pressure ventilation with enflurane in Oxygen. Intra-arterial and central venous pressures were monitored along with arterial gas analyses. Aprotonin was given by slow intravenous bolus followed by 1’000’000 KIU in an infusion. St. Thomas’ Crystalloid Cardioplegic Solution was used during the Cardio Pulmonary Bypass (CPB).